Demographic Profile of Assault Victims in Bikaner Region of Rajasthan – One year institution based cross-sectional study - Gahlot, Vandana; Saini, O P; Kumar, Shalender; Singh, Rajendra; Sharma, Arun (Journal of Forensic Medicine and Toxicology, 2026)
This study comprised of 262 assault cases presented to OPD of FMT department, admitted and brought dead cases in our institution from February 2023 to January 2024. Maximum number of cases recorded in 21-30 years age group (38.54%). Males were predominant (210) than females (52). Maximum number of cases recorded in time period of 4 PM to 12 AM i.e. 155 (59.16%). 72.15% of victims did not gave history of alcohol intake. Status of one case is not known. Perpetrator was known in 84.73% cases and not known in 15.26% cases. Maximum males (64.76%) and females (73.07%) were from urban area. While 35.58% victims were from rural areas. 87.14% males and 88.46% females were Hindu.